Sports rescue : the South End Mustangs professional ice hockey team - Chard, Chris; Spence, Kirsty K. (London : Human Kinetics, Inc., 2015)
Three years ago, Steve Thornton purchased the South End Mustangs, a professional ice hockey team competing in the D1 division in the United Kingdom. Unfortunately, Thornton has experienced challenging times during his ownership tenure. The team has achieved mediocre results on the ice and poor results off the ice. Thornton knows he needs help to turn the Mustangs franchise around. Thus, as a result, he turns to John Tapner, a sport business owner, operator, entrepreneur, and advisor. Tapner is best known as a professional sport consultant and TV personality, representing his company Sports Rescue, which is the same name as his hit television show. When an owner calls Tapner, it is because a professional sports team is in trouble and needs to be rescued.
Originally published in Chard, C., & Spence, K. K. (2015). Sports Rescue: The South End Mustangs professional ice hockey team. Case Studies in Sport Management, 4(1), 44-53. DOI:.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Thornton, Steve, -- active 2015.; Tapner, John, -- active 2015.; South End Mustangs; Sports Rescue; Sports administration -- Great Britain -- Case studies